2014
DOI: 10.5897/ajmr2014.6935
|View full text |Cite
|
Sign up to set email alerts
|

Virulence strategies of phytopathogenic bacteria and their role in plant disease pathogenesis

Abstract: Phytopathogenic bacteria have evolved several virulence strategies to face hostile environment of the host plant. In this article, we reviewed the recent progress in research on characterization of the virulence factors including secretion system with their protein effectors, toxins production, extracellular polysaccharides, growth regulators, cell wall degrading enzymes, biofilm formation, siderophores and their role in the plant infection and symptom development focusing particularly on a group of bacteria s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In fungi and oomycetes, effectors are produced and released by haustoria, which also function as intracellular feeding structures (Wang et al, 2017). In bacterial pathogens, effector proteins are secreted via six secretory systems (Setti et al, 2014). For instance, the type two secretory system (T2SS) also known as sec dependent system release the apoplastic effectors, cell wall degrading enzymes and other hydrolytic enzymes such as cellulases, xylanases, amylases and proteases (Setti et al, 2014;Pfeilmeier et al, 2016).…”
Section: S-nitrosylation Exploited By the Host And Pathogen During Immuno Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fungi and oomycetes, effectors are produced and released by haustoria, which also function as intracellular feeding structures (Wang et al, 2017). In bacterial pathogens, effector proteins are secreted via six secretory systems (Setti et al, 2014). For instance, the type two secretory system (T2SS) also known as sec dependent system release the apoplastic effectors, cell wall degrading enzymes and other hydrolytic enzymes such as cellulases, xylanases, amylases and proteases (Setti et al, 2014;Pfeilmeier et al, 2016).…”
Section: S-nitrosylation Exploited By the Host And Pathogen During Immuno Responsesmentioning
confidence: 99%
“…In bacterial pathogens, effector proteins are secreted via six secretory systems (Setti et al, 2014). For instance, the type two secretory system (T2SS) also known as sec dependent system release the apoplastic effectors, cell wall degrading enzymes and other hydrolytic enzymes such as cellulases, xylanases, amylases and proteases (Setti et al, 2014;Pfeilmeier et al, 2016). Whereas the type three secretory system (T3SS) is the molecular machinery that delivers cytoplasmic effectors into host cells.…”
Section: S-nitrosylation Exploited By the Host And Pathogen During Immuno Responsesmentioning
confidence: 99%
“…Phytopathogenic fungi and oomycetes deliver their effectors employing the transport system of the plant cell [60,61]. The struc ture, characteristics, and features of individual system types delivering pathogen effectors into the cell have been described in detail in several reviews [62][63][64].…”
Section: Effector Triggered Immunity Etimentioning
confidence: 99%
“…Ten strains purified Ascochyta pisi were retained which represent a random sample representative of the areas and visited varieties (Setti et al 2012).…”
Section: Strains Usedmentioning
confidence: 99%
“…In Algeria the anthracnose caused by Ascochyta spp, a disease feared by farmers, but recent studies have shown the spread of anthracnose (Setti et al 2008;Setti et al 2010;Setti et al 2011). During the spring of 2012, continuous rains, accompanied by lower temperatures, a period that has characterized the region of Oran (western Algeria), has fostered the emergence of anthracnose pulses, including small peas (Setti et al 2012). Tivoli et al (1996), reported that the free water on the leaves promotes sporulation.…”
Section: Introductionmentioning
confidence: 99%